2007
DOI: 10.1007/bf02977653
|View full text |Cite
|
Sign up to set email alerts
|

Vinegar- processed ginseng radix improves metabolic syndrome induced by a high fat diet in ICR mice

Abstract: Ginseng has made a successful transition from the world of traditional tonic remedies to conventional medicine, and since the 1920s ginseng root has been documented to be effective in diabetes, hypertension, dyslipidemia and obesity. Based on this wide spectrum of activity we wondered whether ginseng root extract might also be effective in metabolic syndrome (MetSyn). In a series of investigations to develop a potential anti-MetSyn agent, we prepared a vinegar-processed form of ginseng radix (ginsam, GS) and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 17 publications
1
27
0
Order By: Relevance
“…It has been reported that fermentation with Phellinus linteus , Bifidus , or Lactobacillus fermentum shifts the chemical composition of ginsenosides and improves antioxidant, hypolipidemic, hypoglycemic and anti-inflammatory activities [16,17,18,29,30,31]. On the other hand, Red-koji from Monascus species has been used as a medicinal food and fermentation source for other herbs in East Asia including China, Korea and Japan [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that fermentation with Phellinus linteus , Bifidus , or Lactobacillus fermentum shifts the chemical composition of ginsenosides and improves antioxidant, hypolipidemic, hypoglycemic and anti-inflammatory activities [16,17,18,29,30,31]. On the other hand, Red-koji from Monascus species has been used as a medicinal food and fermentation source for other herbs in East Asia including China, Korea and Japan [19].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that RG alleviates obesity-mediated metabolic disorders [10,15]. Moreover, fermentation of RG using a variety of edible microorganisms seems to further enhance the pharmacological efficacy of RG [16,17,18]. Red-koji prepared from Monascus species has traditionally been used as a medicinal food itself and/or as a fermentation source for other herbs in East Asia [19].…”
Section: Introductionmentioning
confidence: 99%
“…Meyer, or Asian ginseng is a commonly used herb in Oriental countries for several purposes (Ang-Lee et al, 2001;Yun et al, 2007;Du et al, 2008). Ginseng reportedly has a myriad of demonstrated effects with regards to cancer, such as anti-angiogenesis, anti-proliferation and apoptosis (Sagar et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In 1984, it was reported that red ginseng saponin showed no significant change of high-density lipoproteincholesterol-cholesterol (HDL-cholesterol) level but it lowered plasma levels of total cholesterol and highly elevated those of triglyceride in Wistar male rats fed on a diet high in cholesterol and triglyceride (86). In 2006, it was identified that Rg 3 (15/16) might be effective in metabolic syndrome (MetSyn) by comparing the anti-MetSyn effect of vinegar-processed ginseng radix and non-processed ginseng radix in a high fat diet induced MetSyn ICR mouse model (87). In the same year, it was reported that red ginseng had a potent antithrombotic effect in vivo, which may be due to antiplatelet rather than anticoagulation activity, and its intake may be beneficial to individuals with high risk of thrombotic and cardiovascular diseases (88).…”
Section: Lipid-regulating and Antithrombotic Activitiesmentioning
confidence: 99%